REASSESSING THE BIOSTRATIGRAPHY AND THE PALEOBATHYMETRY OF THE GONFOLITE LOMBARDA GROUP IN THE COMO AREA (NORTHERN ITALY) - FABRIZIO TREMOLADA; ELISA GUASTI; GIANCARLO SCARDIA; CIPRIANO CARCANO; SERGIO ROGLEDI; DARIO SCIUNNACH (Rivista Italiana di Paleontologia e Stratigrafia, 2010)
Calcareous nannofossil and foraminiferal analyses have been carried out on outcrops from the type-area of the Gonfolite Lombarda Group (Como, northern Italy). In these marine fine- to coarse-grained clastics, rapidly accumulating at the southern front of the uprising Alpine range during the Oligo-Miocene, a scarce, but reliable, sequence of calcareous nannofossil events has been observed, allowing to refine the previous age assignments. Planktonic foraminifera were found to be extremely rare and provided limited biostratigraphic information. The Villa Olmo Conglomerate and the Chiasso Formation contain the Last Occurrence (LO) of Sphenolithus distentus and the First Occurrence (FO) of Triquetrorhabdulus carinatus, which are characteristic of the nannofossil zones NP24 and NP25 (Chattian), respectively. The lower part of the Como Conglomerate was deposited during the zone NP25, whilst the upper part of the Como Conglomerate straddles the Chattian/Aquitanian boundary in zone NN1. The deposition of the Prestino Mudstones also occurred during zone NN1. However, the upper part of this formation has been dated as Burdigalian during nannofossil zone NN2. The deposition of the upper part of the Val Grande Sandstone has been assigned to the NN3 zone owing to the presence of the taxon Sphenolithus belemnos, which is restricted to NN3. The upper part of the investigated section is characterized by the deposition of the Lucino Conglomerate and its fine-grained members (Lucinasco and Lurate Caccivio Mudstones). The Lucinasco Mudstones have been dated as late Burdigalian corresponding to zone NN4, whilst the overlying Lurate Caccivio Mudstones were deposited during the Langhian part of the zone NN5, based on the presence of S. heteromorphus and the absence of H. ampliaperta. On the whole, the base and the top of the outcropping Gonfolite Lombarda Group result from our study to be younger than hitherto proposed, allowing to resolve certain previous conflicts with the few radiometric dates available for clasts from the Gonfolite Lombarda Group. The depth of deposition was upper bathyal during the Chattian and the Aquitanian and shallowed to neritic during the deposition of the Langhian Lurate Caccivio Mudstones.